ISOLATION, MOLECULAR CHARACTERIZATION AND PHA PRODUCTION BY A NOVEL BACILLUS SP., SKM155 FROM POLLUTED WATER - K.CHAITANYA,; P.NAGAMANI,; S.K.MAHMOOD, (International Journal of Pharma and Bio Sciences, 2015)
A polyhydroxyalkonate (PHA) producing Gram-positive, rod-shaped, motile bacterium was isolated from the polluted water pond. Strain SKM-155 grew at 15–45 oC and pH 5.0–9.0 and in the presence of 0–2 % (w/v) NaCl. The strain was catalase-positive and oxidase-positive. Antimicrobial activities were studied. The DNA G+C content was 55.1 mol%. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain is a member of the genus Bacillus and is most closely related to Bacillus invictus Bi.FFUP1T (98.94%), Bacillus altitudinis 41KF2bT (98.34%), Bacillus aerophilius 28KT (98.34%). The sequence of the 16S rDNA gene of strain SKM-155 was determined (1574 bp) and deposited in the EMBL under accession no. LM655321. The major isoprenoid quinine was MK-7 and the polar lipid consisted of diphosphotidylglycerol and an unidentified glycolipid was identified. The major fatty acid are dominated by saturated iso and anteiso (iso-C15:0, anteisoC15:0, anteisoC17:0, isoC17:0). The phenotypic and genotypic properties clearly indicate that strain represents a novel species of the genus Bacillus. The strain produced PHA in mineral medium consisting of glucose and nitrogenous substances. Optimum conditions for polymer production were determined, extracted and confirmed through Spectroscopic and IR analysis.